2021
DOI: 10.1186/s12916-020-01897-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and violence: rising risks and decreasing urgent care-seeking for sexual assault and domestic violence survivors

Abstract: Background There is little information on care-seeking patterns for sexual assault and domestic violence during the COVID-19 pandemic. The objective of this study was to examine the changes in emergency department (ED) admissions for sexual assault and domestic violence since the COVID-19 pandemic was declared. Methods Observational ED admissions data from The Ottawa Hospital were analyzed from March 4 to May 5 (62 days) in 2020 (COVID-19 period) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
2
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 35 publications
4
88
2
13
Order By: Relevance
“…Most EDs saw drastic decreases in all-cause admissions immediately following the COVID-19 lockdown. [13][14][15] Investigations of cause-specific ED admissions varied, where some studies identified increases in IPV or assaultbased cases, 16 17 while others reported decreases. 18 19 Mixed patterns have also been observed in crime data from police departments, where some settings reported increases in domestic violence cases, [20][21][22] some found decreases 23 24 and others identified no detectable changes.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Most EDs saw drastic decreases in all-cause admissions immediately following the COVID-19 lockdown. [13][14][15] Investigations of cause-specific ED admissions varied, where some studies identified increases in IPV or assaultbased cases, 16 17 while others reported decreases. 18 19 Mixed patterns have also been observed in crime data from police departments, where some settings reported increases in domestic violence cases, [20][21][22] some found decreases 23 24 and others identified no detectable changes.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Calls to support services and to the police have varied over the past year, with large increases in most countries, including the UK,3 Brazil,4 and Nepal. Yet, emergency department attendance for domestic violence and non-partner sexual violence has fallen substantially, along with general emergency department attendance 5…”
mentioning
confidence: 99%
“…These ndings echo others' concerns about DVA victims during lockdown [17], and evidence of decreased hospital admissions for DVA, despite social conditions that increase the risk of violence. [22] After the initial drop in referrals at the start of lockdown, both the quantitative and qualitative ndings showed a busy service with increased referrals; the IDVAs continued to provide a robust response, taking on and supporting all cases referred to them. This is notable, particularly considering that DVA is often a hidden problem and detection relies on staff retaining focus on the signs and making sensitive enquiries; staff at the Trust continued to this during lockdown, with intense pressure on hospital services and severe disruption to usual methods of communication.…”
Section: Discussion and Comparison With Existing Literaturementioning
confidence: 98%